Pengaruh Keluarga Dan Pendidikan : Studi Tentang Pengaruh Interaksi Terhadap Prestasi Akademik Siswa - Tsabitha Azra; Dandi Salmanda; Putri Fadilah Batubara; Nadya Dinnul Qoyyimah; Eka Susanti (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This paper reports on a qualitative investigation of several students at one of the state high schools in Medan. Many students lose their academic achievements. For this reason, the author examines students' achievements from where they get their academic achievements. The author's aim in conducting this research is to try to find out how effective the interaction between families and students is in influencing students' academic achievement. With the hope that the author will get results and some interesting conclusions from it. The author used qualitative descriptive using primary data to get results in the form of 74 informants through school data from the number of students they accepted at state universities and 5 of the 74 informants interviewed. This research shows that social interaction in the family has an impact on learning achievement, social interaction in the family, achievement motivation, learning independence. It is important for parents to focus on establishing interactions with their children, because the more frequently they interact, the it will have a lot of positive impacts on student academic achievement.